A Comparison Study of Sampling and Analyzing Volatile Organic Compounds in Air in Kuwait by Using Tedlar Bags/Canisters and GC-MS with a Cryogenic Trap - Hongmao Tang; Khaliq R. Beg; Yousef Al-Otaiba (The Scientific World Journal)
Kuwait experiences desert climatic weather. Due to the extreme hot and dry conditions in this country, some analytical phenomena have been discovered. Therefore, a systematic study of sampling and analyzing volatile organic compounds in air by using GC-MS with a cryogenic trap is reported in this paper. This study included comparisons of using different sample containers such as Tedlar bags and SUMMA canisters, and different cryogenic freezing-out air volumes in the trap. Calibration curves for different compounds and improvement of replicated analysis results were also reported here. The study found that using different sample containers produced different results. Analysis of ambient air samples collected in Tedlar bags obtained several volatile organic compounds with large concentrations compared to using SUMMA canisters. Therefore, to choose a sample container properly is a key element for successfully completing a project. Because GC-MS with a cryogenic trap often generates replicated results with poor agreement, an internal standard added to gas standards and air samples by using a gas syringe was tested. The study results proved that it helped to improve the replicated results.